Pacific cod (Gadus macrocephalus) as a paleothermometer: otolith oxygen isotope reconstruction - West, Catherine F.; Wischniowski, Stephen; Johnston, Christopher (Journal of Archaeological Science, 2012)
Stable isotope studies are increasingly important for understanding past environmental and cultural developments along the North Pacific Rim. In this paper, we present methods for using Pacific cod (Gadus macrocephalus) otoliths as a paleothermometer using a case study from Kodiak Island, Alaska. The results of this study indicate that Pacific cod otoliths record variable paleoenvironmental conditions during the Little Ice Age. The broad distribution of Pacific cod and success in using the otoliths as a paleothermometer makes this method widely applicable to researchers working throughout the northern Pacific Rim.
id: 2303